2021
DOI: 10.1038/s41374-020-00512-2
|View full text |Cite
|
Sign up to set email alerts
|

PAI-1 derived from cancer-associated fibroblasts in esophageal squamous cell carcinoma promotes the invasion of cancer cells and the migration of macrophages

Abstract: Cancer-associated fibroblasts (CAFs) contribute to the progression of various cancers. Previously, we reported the significance of CAFs in esophageal squamous cell carcinoma (ESCC); however, the functions of CAFs in the ESCC microenvironment remain unknown. To investigate CAFs’ function, we established an indirect coculture assay between human bone marrow-derived mesenchymal stem cells (MSCs) and ESCC cells. Cocultured MSCs expressed more fibroblast activation protein, one of the markers of CAFs, compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 46 publications
(71 reference statements)
2
48
0
Order By: Relevance
“…To explore the role of CAFs in the ESCC tumor microenvironment, we established MSC-derived CAF-like cells by indirect co-culture of MSCs with ESCC cells. In a previous study, we compared MSCs and CAF-like cells by cDNA microarray analysis and found that, in the CAF-like cells, MT2A was the most upregulated among the differentially expressed genes [17]. Here, qRT-PCR and Western blotting confirmed that the MT2A mRNA and MT2A protein were highly expressed in all the three types of CAF-like cells (CAF8, CAF9, and CAF15) (Figures 1A,B and S8A).…”
Section: High Expression Of Mt2a In Caf-like Cellssupporting
confidence: 55%
See 3 more Smart Citations
“…To explore the role of CAFs in the ESCC tumor microenvironment, we established MSC-derived CAF-like cells by indirect co-culture of MSCs with ESCC cells. In a previous study, we compared MSCs and CAF-like cells by cDNA microarray analysis and found that, in the CAF-like cells, MT2A was the most upregulated among the differentially expressed genes [17]. Here, qRT-PCR and Western blotting confirmed that the MT2A mRNA and MT2A protein were highly expressed in all the three types of CAF-like cells (CAF8, CAF9, and CAF15) (Figures 1A,B and S8A).…”
Section: High Expression Of Mt2a In Caf-like Cellssupporting
confidence: 55%
“…In our previous study, the three types of CAF-like cells (CAF8, CAF9, and CAF15) enhanced the migration and invasiveness of three types of ESCC cell lines (TE-8, TE-9, and TE-15, respectively) [17]. In this study, we found that while MSCs also enhance the migration and invasiveness of the ESCC cell lines, the effects of CAF-like cells exceed those of MSCs (Figure 3A,B).…”
Section: Igfbp2 Secreted By Caf-like Cells Promotes Migration and Invasion Of Escc Cell Linesmentioning
confidence: 83%
See 2 more Smart Citations
“…Moreover, there was initial evidence suggesting that PAI-1 can affect the biological behavior of inflammatory cells. For example, Sakamoto et al (58) found that PAI-1 that abnormally elevated in esophageal squamous cell carcinoma (ESCC) could promote macrophage infiltration by the Akt and Erk1/2 signaling pathways. And studies indicated that PAI-1 could assist IL-8-mediated neutrophil infiltration via inhibiting IL-8/Heparan Sulfate/ Syndecan-1 Complex shedding on endothelial cell surfaces (59).…”
Section: Treatments Ofmentioning
confidence: 99%